VALIDATION OF SECURITY REQUIREMENTS FOR MOBILE APPLICATION: A STUDY - Kamalrudin, Massila; Sidek, Safiah (2014)
The increased usage of 3G and 4G networks in smartphones has resulted in the need for validating security requirement to ensure safe and secure mobile application experience to users. However, improper validation of security requirements can lead to poor quality of software development. This is also commonly happened while developing software application for mobile. Thus, this paper discusses the gaps found from the existing work on validating the security requirements of mobile application and analyses a few security requirement engineering tools for mobile application that exist in the market for commercial or research purposes. We report our findings from review and analysis of different studies on security requirement engineering for mobile application. The strengths and weaknesses of the features and utility are also presented to provide further understanding of the gaps and weaknesses of each tool. We conclude that these tools are still immature and need further improvements.